2014
DOI: 10.1111/ajt.12526
|View full text |Cite
|
Sign up to set email alerts
|

Costimulation Blockade Alters Germinal Center Responses and Prevents Antibody-Mediated Rejection

Abstract: De novo donor-specific antibody (DSA) after organ transplantation promotes antibody-mediated rejection (AMR) and causes late graft loss. Previously, we demonstrated that depletion using anti-CD3 immunotoxin (IT) combined with tacrolimus and alefacept (AMR regimen) reliably induced early DSA production with AMR in a nonhuman primate kidney transplant model. Five animals were assigned as positive AMR controls, four received additional belatacept, and four received additional anti-CD40 mAb (2C10R4R4). Notably, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
169
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(183 citation statements)
references
References 35 publications
13
169
1
Order By: Relevance
“…We and others have reported that CTLA4-Ig inhibits early T cell-dependent alloantibody responses as well as recall responses (15)(16)(17)(18). In this study, we extend those observations by characterizing the impact of extended CTLA4-Ig treatment on graft-reactive memory T cell responses.…”
Section: Cd57supporting
confidence: 69%
“…We and others have reported that CTLA4-Ig inhibits early T cell-dependent alloantibody responses as well as recall responses (15)(16)(17)(18). In this study, we extend those observations by characterizing the impact of extended CTLA4-Ig treatment on graft-reactive memory T cell responses.…”
Section: Cd57supporting
confidence: 69%
“…37,38 An example of this statement is the efficacy of CD40L/CD40 targeting in preclinical and clinical settings of transplantation and autoimmune disease. 39,40 The data presented herein demonstrate that modulation of BTLA/HVEM pathway does not affect Tfh cell expansion, GC reactions or the de novo formation of host antidonor allogeneic antibodies. BTLA, like other members of the immunoglobulin superfamily, such as CTLA4 and PD1, functions as a co-inhibitory receptor of the immunoglobulin superfamily.…”
Section: Discussionmentioning
confidence: 73%
“…Our studies build upon previous work by others demonstrating that costimulatory signal deliver by helper T cells, predominantly transmitted via the indirect pathway of allorecognition, are required for induction of high titer, isotype switched, IgG, alloantibody reactive to donor antigens (7,8,10,(30)(31)(32)(33)(34)(35)(36). Using an allosensitization model in which the prior administration of a single fully MHC disparate splenocyte dose provides sufficient high-titer alloantibody to reject allogeneic BM grafts even 1 year postpriming, we newly demonstrate that only a combination of a highly depletionary anti-CD20 mAb plus LTbR-Ig that reduces GC formation sufficiently eliminates alloantibody to permit donor BM rescue of lethally irradiated, T-and NK-depleted recipients ( Figure 5D).…”
Section: Discussionsupporting
confidence: 67%